Physical Mechanisms Affecting the Reliability of GaN-based High Electron Mobility Transistors. Issue 1792 (18th May 2015) - Schrimpf, R. D.; Fleetwood, D. M.; Pantelides, S. T.; Puzyrev, Y.S.; Mukherjee, S.; Reed, R. A.; Speck, J. S.; Mishra, U. K.
ABSTRACT: The physical mechanisms responsible for electrically-induced parametric degradation in GaN-based high electron mobility transistors are examined using a combination of experiments, device simulation, and first-principles defect analysis. A relatively simple formulation is developed under the assumption that the hot-electron scattering cross-section is independent of the electron energy. In this case, one can relate the change in defect concentration to the operational characteristics of a device, such as the spatial and energy distribution of electrons (electron temperature), electric field distribution, and electron energy loss to the lattice.